DAMPAK MODEL PEMBELAJARAN STAD TERHADAP KEMAMPUAN MEMBACA EKSTENSIF TEKS BERITA PESERTA DIDIK MTs HALABAN TAHUN PELAJARAN 2014-2015 - Silvianti Silvianti (JELISA (Jurnal Edukasi dan Literasi Bahasa), 2020)
This research was doing to know the effect of STAD method to improve exstensive reading texs ability students of MTsS Halaban in 2014-2015 academic year. The population and sample of this research the students of eight class. The research method used is descriptive method. The data gathering by using observation, triangulation, and full participant. Analysis of the data qualitative and also by using numeric and percentace. Research design used is planning, acting, observing, and reflecting was consist of three cycles. The result of the three cycles showed the improvement of students’ average score. The students’ average score in Pre-Test were 48,27; at the end of the first cycle the students’ average scores were 64,00; at the test of the second cycle students’ average score achieve 82,70; and at the last test of the third cycle students’ average score achieve 86,70. It means that the STAD method in learning activities can improve reading extensive texs ability.